Visualisasi Data Opini Publik pada Media Sosial Twitter (Studi Kasus : Nusantara Sebagai IKN Indonesia) - Dharmendra, Komang; Januhari, Ni Nym Utami; Diaz, Ricky Aurelius Nurtanto; Ramayasa, I Putu; Putra, I Made Agus Wirahadi (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
The capital city has an important role for various aspects of government, the capital city has a function as the center of political power and the economy of a country. In the process, sometimes the head of government of a country moves the capital of the country, either moving it to an existing city or building a new city that was built specifically to become the capital of the country. Like what Indonesia did, which planned to move the country's capital, which was previously in Jakarta, moved to East Kalimantan and built a new city to become the nation's capital with the name Nusantara. The relocation of the capital city was carried out to divide the economic center and the government center which were previously centered in Jakarta into an economic center in Jakarta and a government center in the archipelago. The announcement of the name of Indonesia's new capital city received reactions from the public, with various written opinions being shared through social media. One of the social media channels that is widely used is Twitter. With so many public responses through social media, a process is needed to find out how to respond and form of expression for the announcement of the name of the capital city of the archipelago. One of the processes that can be done is to visualize tweets containing the word "Nusantara" which collected 83604 tweets using data on the number of tweets, posting hours, hashtags that can find out how the public responds to the announcement of the state capital "Nusantara"..